Dog Man: Brawl of the Wild #6 - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2019)
When Dog Man is sent to the pound for a crime he did not commit, his friends work to prove his innocence.
Fore-foreward: Behind the Profundity -- Foreword: George and Harold's recap of our story thus far -- Two messages -- The Sad Guys -- Things get worse -- A buncha stuff that happened next -- Dog jail blues -- Even more stuff happens -- Girl power -- Help is on the way -- Dog Man: The major motion picture -- The great cat's bee -- March of the misfits -- Sarah hatoff news blog -- How to draw.
"Treehouse Comix proudly presents."
New Kids Book 2023 Spring.
Keywords: Adventure and adventurers -- Fiction; Dogs -- Fiction; Cats -- Fiction; Police -- Fiction; Humorous fiction; Graphic novels